Gonadectomy influences blood pressure through the kallikrein-kinin system - Azurmendi, Pablo Javier (2009)
The kallikrein-kinin system (KKS) appears to be involved in blood pressure regulation. We showed that ovariectomy (oVx) stimulates urinary kallikrein activity (UKa). So, we test whether gonadectomy (Gx) would affect blood pressure through an increase in KKS activity and which mechanism(s) were involved. We studied adult Wistar rats of either sex, with and without Gx. At baseline all groups were normotensive although the oVx mean arterial pressure (MAP) was lower than female MAP (p < 0.05). KKS blockade by aprotinin increased MAP (p < 0.05) exclusively in the oVx group. The probably mechanism(s) involved in KKS regulation (synthesis, renal content and UKa) were also studied. Previous Gx, kallikrein content (nkat/g kidney weight) and UKa (nkat/g kidney weight/day) were higher in female than in male rats: 12 ± 1.1 versus 6 ± 0.7 and 40 ± 6.8 versus 26 ± 3.4, respectively. After Gx, kallikrein content increased significantly in both orchiectomized (oRx) and oVx rats, and UKa showed a similar tendency (NS). Kallikrein synthesis did not show gender difference in non-Gx rats, but an increase after oVx was observed. KKS was found to be involved in blood pressure regulation in oVx animals. oVx may trigger the increase in kallikrein synthesis and content and UKa to act upon blood pressure.